Terrorism New Wave: The Same Style but New Ways in the Context of Online Radicalization - Muhammad Asad Latif (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Radicalization, which is influenced by social, cognitive, and economic variables, is the mental process that justifies violence or violent behavior. Since the invention of the Internet radical organizations have modified their tactics in order to fit the new environment. The Internet has evolved into more than simply a platform for extremist activity; it has also taken the place of the main operating environment and arena where political beliefs are developed, assaults are planned, and exceptional social movements start to take shape. Members of the group meet up online to discuss their religious beliefs and utilize these forums to broaden the scope of action at the individual and organizational levels in order to disseminate their political ideology, hire employees, and organize assaults. The conceptual framework, individual and group dynamic reasons of radicalization, metaphors for describing radicalization, radicalization driven by religion, internet radicalization, and case studies are highlighted in the current study.